Pengembangan Sistem Informasi Kesehatan Gizi (Studi Kasus: Klinik UB Malang) - Aizul Faiz Iswafaza; Achmad Arwan; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of human welfare is derived from the value of health. For health, it is obtained by maintaining food intake for the body. Maintaining food intake can be done in consultation with experts or the application of a balanced diet. Universitas Brawijaya Malang Clinic is one of the nutrition health service providers. The clinic conducts services based on the Hospital Nutrition Guidelines book in 2011. The services carried out are in the form of recording personal data until monitoring and evaluation. Recording patient data currently using conventional methods, causing limited access to patient data services. In making a diet menu design the patient needs food data and does not exceed the patient intervention limit. This study aims to develop an information system that assists nutritionists in serving the nutritional health of patients using the waterfall development method. The technology used to develop the system is the use of laravel frameworks with the website programming language. In making system requirements engineering, 30 functional requirements were obtained which were then made designs and then implemented. In the final stage of the study, testing was carried out using the black box and white box method. The results of the black box testing of 30 functional requirements found 52 test cases that gave a valid status of 100% which meant that it was in accordance with the design made.